FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG KIOS DI DESA LIMEHE TIMUR KECAMATAN TABONGO KABUPATEN GORONTALO - Sri Hantuti Paramata; Salman Hasan; Harijono Imbran (Universitas Muhammadiyah Gorontalo, 2026)
This study aims to determine kiosk vendors' income and the factors influencing their income in Limehe Timur Village, Tabongo District, Gorontalo Regency. This research employed a descriptive quantitative approach using questionnaires distributed to 32 respondents. The data were analyzed using multiple linear regression and multiple correlation, preceded by hypothesis testing. The results showed that simultaneously length of business (X1), business location (X2), and working hours (X3) significantly influenced kiosk vendors' income. Partially, working hours had no effect on kiosk vendors' income, while length of business and business location had a positive effect on kiosk vendors' income.